1991
DOI: 10.1113/jphysiol.1991.sp018524
|View full text |Cite
|
Sign up to set email alerts
|

Role of small diameter afferents in reflex inhibition during human muscle fatigue.

Abstract: SUMMARY1. Previous work has shown that the H reflex excitability of the human soleus motoneurones is reduced during fatigue and is accompanied by a corresponding decrease in electromyographic (EMG) activity during maximal voluntary contractions. These findings were consistent with the existence of a reflex whereby xmotoneurones are inhibited by sensory input from the fatigued muscle.2. To elucidate the contribution of different-sized afferents in such reflex inhibition, compression of the sciatic nerve was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
151
3
10

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(172 citation statements)
references
References 22 publications
8
151
3
10
Order By: Relevance
“…Because of the slow time course of the H reflex decrease during fatigue, it is suggested that this is induced by muscle metabolic or chemical processes which could be mediated by small diameter afferents from the fatigued muscle (Garland, 1991). This conclusion is supported by our finding that the H reflex decrease does not recover as long as ischaemia is maintained (cf.…”
Section: Discussionsupporting
confidence: 81%
“…Because of the slow time course of the H reflex decrease during fatigue, it is suggested that this is induced by muscle metabolic or chemical processes which could be mediated by small diameter afferents from the fatigued muscle (Garland, 1991). This conclusion is supported by our finding that the H reflex decrease does not recover as long as ischaemia is maintained (cf.…”
Section: Discussionsupporting
confidence: 81%
“…The reduced motoneuronal excitability probably contributes to the decline in the discharge rate of single motor units and the development of central fatigue that occurs with sustained MVCs. The reduction in motoneuron firing rates observed in many studies (Grimby et al, 1981;Bigland-Ritchie et al, 1983;Gandevia et al, 1990) has often been attributed to reflex inhibition from group III and IV muscle afferents (Woods et al, 1987;Garland, 1991). In the current study, when ischemia was maintained after fatiguing contractions of elbow extensors, CMEPs in triceps failed to recover.…”
Section: Discussionmentioning
confidence: 50%
“…Much of the indirect evidence favoring a reflex inhibitory pathway mediated by group III and IV muscle afferents has been obtained for other physiological extensors. For example H-reflexes evoked in ankle plantarflexors are depressed after fatigue (Garland and McComas, 1990;Garland, 1991;Loscher et al, 1996;Walton et al, 2002;Kuchinad et al, 2004). We suggested previously that the discrepancy between results based on the H-reflex and that for the CMEP in elbow flexors (Butler et al, 2003) could be attributable to presynaptic inhibition of group Ia afferent volleys by group III and IV muscle afferents (Pettorossi et al, 1999;Rossi et al, 1999;Rudomin and Schmidt, 1999).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, fascicle length afferent information coming from the muscle spindles can also be ruled out as possible excitability modulator, since FL was the same among the experimental protocols. (4) small diameter afferents (i.e chemosensors and nociceptors; Gandevia 1998;Garland et al 1991) should play if any a small role as the maximal effort duration was small (Min:2.35s/Max:3.4s) and the recovery time between trials was long (3 minutes). The torque analysis for each trial throughout the testing session showed no significant effect of fatigue (see methods), therefore it seems that the effort to rest ratio probably was not enough to cause metabolite accumulation and induce peripheral fatigue; (5) corticospinal descending drive produced by TMS reduced PSI of Ia terminals of a relaxed muscle (Meunier & Pierrot-Deseilligny 1998) suggesting that the same cortical sites both activate MNs of a given pool and depress primary afferent depolarization interneurons.…”
Section: Discussionmentioning
confidence: 99%